RANCANG BANGUN PENGATUR NUTRISI OTOMATIS PADA TANAMAN HIDROPONIK - Listiana, Reni Listiana; Sjahrul, Yurika; Ramdani, Ryan (Jurnal TEDC; Vol 18 No 3 (2024): JURNAL TEDCDO - 10.70428/tedc.v18i3.860, 2024)
Agriculture is one of the most important sectors for society. Along with the times, many agricultural lands have been turned into residential areas, especially in office areas. Urban farming is a solution to overcome the limited land for farmingTherefore, there is a need for an innovation in the Hydroponic method, namely by making an automatic nutrient regulator in hydroponic plants. This research aims to make the provision of nutrients in hydroponic plants effective and efficient, as well as ease of monitoring by controlling through a smartphone. Controlling the actuator in the form of a pump can be done manually with keystroke instructions and can be done automatically with instructions based on the comparison of sensor readings and setpoints, namely if 1400 the regular water pump is on the nutrient pump is off, while if >=1050 and <=1400 both the nutrient pump and the regular water pump are off. Monitoring of nutrient levels (ppm) and water levels will continue to be displayed on the LCD and Blynk application both in manual mode and during automatic mode. The final result of testing this tool is found that the use of sensors in reading the value of nutrients (ppm) and adjusting the water level is more effective than manual nutrition. Because the sensor will intensely control the nutrient content needed by plants and the appropriate water level for Hydroponic plants. Monitoring of nutrient levels (ppm) and water levels can be seen through the LCD and in the Blynk application. The process of providing nutrients is done by controlling the pump to flow based on the instruction of the button press or based on the sensor reading with the setpoint.